Implementasi Framework Codeignter Untuk Pengembangan Website Pada Dinas Perkebunan Provinsi Kalimantan Tengah - tyowati, Sulis; Irawan, Rio (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
Implementation Framwork CodeIgniter at Plantation Office of Central Kalimantan Province aims to deliver profile information, commodity prices, business partners, announcements, official agenda, gallery activities as well as downloaded files. Method used in this study includes data collection methods (literature review, interviews) and methods of analysis, namely data analysis and systems analysis. The analysis system used is PIECES analysis. With this website visitor facilities in seeking information about the price of commodities, the announcement and the agenda of the services, download files plantations and can see photos and video activities Plantation Office of Central Kalimantan Province and features that allow visitors to be more efficient in finding the necessary information and features more than the previous blogspot media.